Crafting for autonomy, competence, and relatedness: A self‐determination theory model of need crafting at work. - Olafsen, Anja H.; Marescaux, Baptiste P. C.; Kujanpää, Miika (Applied Psychology: An International Review, 2025)
With the purpose of extending job crafting theory, the current article outlines a comprehensive conceptual model of work‐related need crafting grounded in self‐determination theory—the Self‐Determination Theory Model of Need Crafting at Work. Specifically, by taking as our basis the three basic psychological needs for autonomy, competence, and relatedness, we introduce the concept of work‐related need crafting and outline its underlying cognitive and behavioral components. We also theorize how cognitive and behavioral forms of need crafting are related and how cognitive and behavioral need crafting foster well‐being and optimal functioning by enhancing need satisfaction and reducing need frustration. Finally, we outline a reciprocal relation between need crafting practices and the experience of basic psychological needs, and thereby depict how need crafting and basic psychological needs develop over time. In sum, the Self‐determination Theory Model of Need Crafting at Work provides a theory‐based framework relevant for covering a wide breadth of different need crafting practices that have the potential to significantly advance future research on job crafting for the benefit of both employees and organizations.